Statistics?

Algebra Level 3

The elements of set S S of real numbers with cardinality n n form an arithmetic progression with common difference d d . Express the population standard deviation of set S S in terms of n n and d d .

An example of set S S is 2, 5, 8, 11, 14, 17 \text{{2, 5, 8, 11, 14, 17}} . It has cardinality 6, and its elements form an AP with common difference 3.

σ = d 6 3 ( n 2 1 ) \sigma=\frac{d}{6}\sqrt{3(n^2-1)} σ = d ( n 1 ) 6 3 \sigma=\frac{d(n-1)}{6}\sqrt 3 σ = d 3 6 ( n 2 + 1 ) \sigma=\frac{d}{3}\sqrt{6(n^2+1)} None of the above

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let S i S_{i} , be an element of the set S S . Because the elements of set S S form an arithmetic progression we have:

S = { A + d , A + 2 d , . . . , A + ( n 2 ) d , A + ( n 1 ) d } . S = \{A+d, A+2d, ... , A + (n-2)d, A + (n-1)d\}.

We could set A = 0 A = 0 because standard deviation is not affected by adding a constant to each of the elements of the set. To calculate we'll use the following formula:

σ 2 = < x 2 > < x > 2 { \sigma }^{ 2 }=\left< x^{ 2 } \right> -{ \left< x \right> }^{ 2 }

where,

< x > = 1 n x i = 1 n k = 1 n ( k 1 ) d = 1 n ( 0 + d + 2 d + . . . + ( n 1 ) d ) = d n ( 1 + 2 + 3 + . . . + ( n 1 ) ) ; 1 + 2 + . . . + k = k ( k + 1 ) 2 = d n ( n 1 ) n 2 = ( n 1 ) d 2 \left< x \right> =\frac { 1 }{ n } \sum { { x }_{ i } } =\frac { 1 }{ n } \sum _{ k=1 }^{ n }{ (k-1)d } \\ \qquad =\frac { 1 }{ n } (0+d+2d+...+(n-1)d)\\ \qquad =\frac { d }{ n } (1+2+3+...+(n-1));\quad 1+2+...+k=\frac { k(k+1) }{ 2 } \\ \qquad =\frac { d }{ n } \frac { (n-1)n }{ 2 } \\ \qquad =\frac { (n-1)d }{ 2 }

and

< x 2 > = 1 n x i 2 = 1 n k = 1 n ( k 1 ) 2 d 2 = 1 n ( 0 + d 2 + 4 d 2 + . . . + ( n 1 ) 2 d 2 ) = d 2 n ( 1 + 4 + . . . + ( n 1 ) 2 ) ; 1 + 2 2 + 3 2 + . . . + k 2 = k ( k + 1 ) ( 2 k + 1 ) 6 = d 2 n ( n 1 ) ( n ) ( 2 n 1 ) 6 = d 2 ( n 1 ) ( 2 n 1 ) 6 \left< { x }^{ 2 } \right> =\frac { 1 }{ n } \sum { { x }_{ i }^{ 2 } } =\frac { 1 }{ n } \sum _{ k=1 }^{ n }{ { (k-1) }^{ 2 }{ d }^{ 2 } } \\ \qquad =\frac { 1 }{ n } (0+{ d }^{ 2 }+4{ d }^{ 2 }+...+{ (n-1) }^{ 2 }{ d }^{ 2 })\\ \qquad =\frac { { d }^{ 2 } }{ n } (1+4+...+{ (n-1) }^{ 2 });\quad 1+{ 2 }^{ 2 }+{ 3 }^{ 2 }+...+{ k }^{ 2 }=\frac { k(k+1)(2k+1) }{ 6 } \\ \qquad =\frac { { d }^{ 2 } }{ n } \frac { (n-1)(n)(2n-1) }{ 6 } \\ \qquad =\frac { { d }^{ 2 }(n-1)(2n-1) }{ 6 } \\ \qquad .

Plugging into the first equation:

σ 2 = d 2 ( n 1 ) ( 2 n 1 ) 6 d 2 ( n 1 ) 2 4 σ 2 = d 2 ( n 1 ) 12 ( 2 ( 2 n 1 ) 3 ( n 1 ) ) σ 2 = d 2 ( n 1 ) 12 ( 4 n 2 3 n + 3 ) σ 2 = d 2 ( n 1 ) ( n + 1 ) 12 σ 2 = 3 d 2 ( n 2 1 ) 36 σ = d 6 3 ( n 2 1 ) { \sigma }^{ 2 }=\frac { { d }^{ 2 }(n-1)(2n-1) }{ 6 } -\frac { { d }^{ 2 }{ (n-1) }^{ 2 } }{ 4 } \\ { \sigma }^{ 2 }=\frac { { d }^{ 2 }(n-1) }{ 12 } (2(2n-1)-3(n-1))\\ { \sigma }^{ 2 }=\frac { { d }^{ 2 }(n-1) }{ 12 } (4n-2-3n+3)\\ { \sigma }^{ 2 }=\frac { { d }^{ 2 }(n-1)(n+1) }{ 12 } \\ { \sigma }^{ 2 }=\frac { 3{ d }^{ 2 }({ n }^{ 2 }-1) }{ 36 } \\ \sigma =\frac { d }{ 6 } \sqrt { 3({ n }^{ 2 }-1) } .

That's it!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...